Implantable Neuroamplifers for Electrocorticography Using Flexible and Biocompatible Technology. Issue 13 (5th May 2020) - Marcoleta, Juan Pablo; Nogueira, Waldo; Yoma, Néstor Becerra; Wuth, Jorge; Jakimovski, Filip; Fuenzalida, Victor M.; Doll, Theodor
Abstract : Brain signals such as electroencephalography (EEG) and electrocorticography (ECoG) are used to diagnose epilepsy. ECoG signals are small and therefore require large amplification while keeping the recording electronics small enough to adapt to the surface of the brain. Moreover, the components have to be of low power to reduce the risk of brain damage while recording the brain. Herein, a neuroamplifier that is integrated in an ECoG is described. The amplifier, in combination with a novel multiplexing system that reduces the number of required amplifiers and ensures the flexibility of the ECoG, achieves the desired signal‐to‐noise ratio while reducing power consumption. The feasibility of the proposed design is validated though electronic simulations for different input signals, analyzing the actual amplification achieved and the response times. Moreover the circuit is implemented and real measurements are provided validating the simulations. Abstract : A neuronal amplifier that is combined with an analogue multiplexing system to record brain signals is described. Herein, how the gain bandwidth product conditions the design of the amplifier for analogue sampled signals is discussed.